Mercury and cadmium in striped dolphins (Stenella coeruleoalba) stranded along the Southern Tyrrhenian and Western Ionian coasts - ESPOSITO, MAURO; CAPOZZO, DANIELA; SANSONE, DONATO; LUCIFORA, GIUSEPPE; LA NUCARA, RAFFAELLA; PICAZIO, GIUSEPPE; RIVERSO, CATERINA; GALLO, PASQUALE (Mediterranean Marine Science, 2020)
Pollution by heavy metals is becoming a serious threat to food safety and the health of humans and marine animals in many areas, including the Mediterranean Sea. Cadmium and mercury are among the most toxic of these metals. Their presence in various environmental compartments, which is partly due to human activity, inevitably leads to their bioaccumulation in the food chain. In this study, levels of cadmium and mercury were determined by means of Atomic Absorption Spectrophotometry in liver, kidney and muscle tissues of specimens the dolphinid Stenella coeruleoalba stranded at various locations in coastal areas of the Tyrrhenian and Ionian Sea in Southern Italy from 2015 to 2018. The data were compared with those reported for other Mediterranean locations. Correlations between biometric data (body length, weight and gender) and cadmium and mercury concentrations in tissue samples from these specimens were statistically analyzed in order to investigate the risk that these contaminants may pose to the health of delphinids. Examination of the pattern of contaminants revealed a significantly high concentration of mercury in all the matrices analyzed (liver, kidney and muscle tissue). By contrast, elevated concentrations of cadmium were found only in liver (range: 0.005 - 8.95 mg/kg w.w.) and kidney (range: 0.005 - 34.1 mg/kg w.w.), owing to the accumulator role of these organs during long-term exposure.